2008
DOI: 10.4319/lo.2008.53.6.2462
|View full text |Cite
|
Sign up to set email alerts
|

Nickel limitation and zinc toxicity in a urea‐grown diatom

Abstract: When growing on urea as a nitrogen source, diatoms must accumulate nickel (Ni), a cofactor in the urease enzyme, which hydrolyzes urea. The uptake of Ni at low ambient concentrations is particularly challenging in view of the slow rate of reaction of the Ni 2+ ion with uptake ligands. As expected, cultures of the model diatoms Thalassiosira weissflogii and Thalassiosira pseudonana become limited at very low Ni concentrations when growing on urea but not on nitrate or ammonium as a nitrogen source. At high Ni c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…No significant difference in expression of the urease enzyme was detected between the Fe-replete and Fe-limited cultures. Although previous reports have observed the urease enzyme to be present under Fe and N limitation [19], [47], urease requires nickel (Ni) as a cofactor when processing urea [60], [61]. The Ni-ABC transporter (NikA) was identified to be the most down-regulated protein in Fe-limited cells (−2.87 fold; Table S2).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…No significant difference in expression of the urease enzyme was detected between the Fe-replete and Fe-limited cultures. Although previous reports have observed the urease enzyme to be present under Fe and N limitation [19], [47], urease requires nickel (Ni) as a cofactor when processing urea [60], [61]. The Ni-ABC transporter (NikA) was identified to be the most down-regulated protein in Fe-limited cells (−2.87 fold; Table S2).…”
Section: Discussionmentioning
confidence: 96%
“…The Ni-ABC transporter (NikA) was identified to be the most down-regulated protein in Fe-limited cells (−2.87 fold; Table S2). Egleston and Morel [60] demonstrated that the presence of Ni is essential for urease when diatoms are using urea as their primary N source. The down-regulation of the Ni-transporting enzymes suggests that urease was not actively utilized and urea was not a primary N source during Fe limitation.…”
Section: Discussionmentioning
confidence: 99%
“…In surface waters, Ni speciation is dominated by complexation with organic ligands (Xue et al 2001). Ni limitation has been observed in the marine diatom Thalassiosira weissflogii when provided with urea as nitrogen source, as the diatom requires Ni for use as a cofactor with the urease enzyme (Egleston and Morel 2008;Price and Morel 1991). It has been suggested that in marine systems, partial complexation of Ni to organic ligands and the slow reaction kinetics of Ni exchange reactions may result in Ni limitation (Price and Morel 1991).…”
Section: Nickel In Escherichia Colimentioning
confidence: 98%
“…However, in field studies with diverse plankton assemblages, it has been difficult to distinguish which phytoplankton taxonomic group contributes the largest percentage of community urease activity (Solomon 2006). Urease activity in larger phytoplankton may be inhibited from a lack of Ni 2+ (needed for the metallocenter of urease; Oliveira & Antia 1986, Egleston & Morel 2008 or by metabolites produced in the cell (urease activity measured in in vitro assays decreases with increasing biomass in the assay; Solomon et al 2007). It has also been observed that most urea uptake in the field may be by eukaryotic phytoplankton, while much of the urease activity may be due to smaller phytoplankton and bacteria (Solomon 2006).…”
Section: Regulation Of Urea Catabolismmentioning
confidence: 99%